2001
DOI: 10.1080/08964280109595779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music on Anxiety of Women Awaiting Breast Biopsy

Abstract: The authors investigated the effect of music on the state anxiety of a sample of 20 patients awaiting breast biopsy at a suburban medical facility. The patients were assigned alternately to either the control or experimental group. The individuals in the experimental group were given a 20-minute music-based intervention in a preoperative holding area, whereas the patients in the control group received the customary preoperative care. Clinicians measured blood pressure, heart rate, and respiration in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 12 publications
0
120
0
4
Order By: Relevance
“…31 Furthermore, other studies have shown statistically significant decreases in BP, 32 HR, 5 and RR. 33 We determined that listening to music caused statistically significant decreases in SBP, DBP, HR, and RR levels. Contrary to our findings, Lee et al found that listening to music made no statistically significant impact on BP, HR, and RR in patients undergoing day procedures, 34 while Buffum et al observed that patients who listened to music for 15 min while waiting for vascular angiography procedures experienced no noticeable change in BP and RR, when compared with control group patients.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, other studies have shown statistically significant decreases in BP, 32 HR, 5 and RR. 33 We determined that listening to music caused statistically significant decreases in SBP, DBP, HR, and RR levels. Contrary to our findings, Lee et al found that listening to music made no statistically significant impact on BP, HR, and RR in patients undergoing day procedures, 34 while Buffum et al observed that patients who listened to music for 15 min while waiting for vascular angiography procedures experienced no noticeable change in BP and RR, when compared with control group patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies using the STAI as an outcome measure in breast carcinoma patients have demonstrated a lessening of anxiety with short-term interventions. [67][68][69][70] There is little evidence of a long-term impact. However, studies conducted with other patient populations have shown that a change in depression is usually accompanied by a change in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Results of the meta-analysis are shown in Figures 2-4. It should be noted that some of the studies included only mechanically ventilated patients while others did not include any.…”
Section: Baseline Characteristicsmentioning
confidence: 99%